Proximity marketing in banking: lessons from retail and entertainment industries. (20th January 2020) - Margulis, Anna; Levesque, Nataly; Boeck, Harold
Ubiquitous technologies such as radio frequency identification (RFID) are increasingly being used by organisations to enhance customer experience. This study aims to discover new opportunities to improve customer experience in banking with ubiquitous technologies. The following steps were taken. We determined if and how RFID is being used in the banking industry to enhance customer experience by analysing case studies based on secondary data. We then compared these findings with cases from the entertainment and retail industries as these industries are leading the way in improving customer experience with proximity marketing strategies. The study found only three banking cases where RFID is used to improve customer experience. Our analysis indicates that banks mainly use RFID technology to increase service efficiency and customer convenience and that the potential offered by this innovation is clearly underutilised.